First report of soft rot caused by Pectobacterium carotovorum subsp. carotovorum on cucumber in Malaysia. - Nazerian, Eisa; Sijam, Kamaruzaman; Mior Ahmad, Zainal Abidin; Vadamalai, Ganesan (American Phytopathological Society (APS Press), 2011)
In Malaysia, cucumber is produced in a warm, humid climate, thus the plant is susceptible to attack by P. carotovorum at any time during production. In 2010, cucumber samples with wilted and chlorotic leaves, water-soaked lesions, and collapsed fruits were found in multiple fields. On the basis of biochemical and morphological characteristics, PCR-based pel gene and characterization of the ITS region, digestion of the ITS-PCR products with RsaI restriction enzyme, and pathogenicity tests, the causal agent was identified as P. carotovorum subsp. carotovorum. This is thought to be the first report of soft rot caused by P. carotovorum subsp. carotovorum on cucumber from Malaysia.